Electrochemiluminescence for Characterizing the Polymerization Process during Graphitic Carbon Nitride Synthesis. Issue 14 (23rd July 2019) - Wei, Jingjing; Zhao, Panpan; Chen, Lichan; Tian, Libing; Wu, Haishan; Dong, Yongqiang; Chi, Yuwu; Zhou, Shu‐Feng
Abstract: The physicochemical properties and application performances of graphitic carbon nitride (g‐CN) are highly dependent on its polymerization degree, thus a facile method for screening the polymerization degree is highly desired. Here, electrochemiluminescence (ECL) is creatively employed as an effective tool to achieve this goal. Extension of π‐system and change in pedant groups during g‐CN polymerization process are characterized by g‐CN nanosheets/dissolved oxygen (CNNS/O2 ) and Ru(bpy)3 2+ /CNNS co‐reactant ECL systems, respectively. Linear intensity enhancement along with positive shift in the onset and peak potentials of cathodic CNNS/O2 ECL, as well as linear intensity decreasing in anodic Ru(bpy)3 2+ /CNNS ECL, are observed during polymerization of dicyandiamide to g‐CN, suggesting the feasibility of ECL on studying the polymerization degree. The ECL method would provide a promising prospect for novel properties exploration and application performances optimization of g‐CN. Abstract : Electrochemiluminescence is used to characterize the extension of π‐system and change in pedant groups during graphitic carbon nitride (g‐CN) polymerization process by using g‐CN nanosheets (CNNS)/O2 and Ru(bpy)3 2+ /CNNS co‐reactant ECL systems.